A fireproof recycled composite board taking waste wind power blade fragments as a main base material and a preparation method thereof

CN122916599APending Publication Date: 2026-10-16BEIJING ZHONGCHENG YONGXIN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214001.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

本发明以废弃风电叶片碎料为主要基材,通过溶胀-分步矿化-封闭的预处理路线在碎料表面形成无机矿化层,辅以硅灰石调节基材热膨胀系数、活性氧化镁-微硅粉复合物提供自愈合与体积稳定功能,以及短切玄武岩纤维增强力学性能,由此改善叶片碎料与无机基材界面不相容及热失配导致的服役微损伤累积问题,同时缓解火灾工况下微裂纹贯通和树脂热解产气助燃的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of waste wind power blade scraps as main base material fireproof recycled composite board and preparation method thereof, belong to solid waste resource and building material technical field.The method is broken after decommissioning wind power blade, solvent swelling is carried out in turn, silicate and chloro-salt step mineralization, fluorosilicate closed treatment, obtain the surface of the broken material with inorganic mineralization layer, again with inorganic cementing material, wollastonite, active magnesium oxide-microsilica compound, chopped basalt fiber and water are mixed, by injection molding curing is made into fireproof recycled composite board.The application is improved by swelling-step mineralization-closed pretreatment route, the interface compatibility of blade scrap and inorganic base material, relieves the thermal mismatch stress concentration, inhibits the cumulative service micro-damage, reduces the water absorption of mineralization layer simultaneously, so that the board is suitable for outer wall thermal insulation decorative integrated board core layer, meets long-term service durability and fire safety requirements under fire condition simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste resource utilization and building materials technology, specifically a fireproof recycled composite board with waste wind turbine blade fragments as the main substrate and its preparation method. Background Technology

[0002] Wind turbines are typically designed for a service life of 20-25 years. As early-operated units gradually enter their decommissioning cycle, the pressure to dispose of wind turbine blades continues to increase. The main body of wind turbine blades is made of glass fiber reinforced epoxy resin thermosetting composite material, with some areas containing polyurethane bonding materials. This material exhibits high chemical stability and is difficult to degrade naturally. Traditional landfill disposal occupies a large amount of land, and under long-term storage conditions, the organic additives and microfibers in the composite material pose a potential risk of soil and groundwater pollution. Incineration easily generates air pollutants, and the molten glass fiber residue is difficult to dispose of, easily causing secondary pollution. Against this backdrop, developing a resource-based regeneration route for decommissioned blades suitable for large-scale disposal is an urgent problem that the wind power industry needs to solve.

[0003] Crushing retired wind turbine blades into scrap and using it as a base material for producing building composite panels is a promising approach to waste disposal. In integrated exterior wall insulation and decoration panel systems, the core layer panel provides structural support for the insulation layer and directly determines the fire safety performance of the exterior wall system. In recent years, fire safety control standards for building exterior walls have been continuously tightened, requiring core layer panels to have high combustion performance ratings to prevent the formation of flame propagation channels in a fire. This application scenario provides a potential direction for the resource utilization of wind turbine blade scrap, while also imposing stringent requirements on the long-term reliability of the panels. However, there are two key technical drawbacks when directly using wind turbine blade scrap to prepare the aforementioned core layer panels.

[0004] First, there are interfacial incompatibilities and thermal mismatch issues between blade fragments and inorganic substrates, which easily lead to the accumulation of micro-damage during service. The fragments obtained from the mechanical crushing of retired blades are coated with cured thermosetting resin. The resin layer has low surface energy and weak chemical activity, making it difficult to form an effective interfacial bond with inorganic cementitious materials such as magnesium oxychloride cement, silicate cement, and gypsum. The interfacial area naturally has weak defects. At the same time, the irregular shape and sharp edges of the blade fragments, along with the significant difference in thermal expansion coefficients with the inorganic substrate, constitute a thermal mismatch system. Under the service environment of the exterior wall, the core panel is subjected to repeated expansion and contraction caused by diurnal temperature differences, alternating wet and dry conditions, and wind and rain erosion. The cyclic stress generated by thermal mismatch continues to act on the weak points of the interface, gradually inducing microcracks. The sharp edges of the fragments are prone to stress concentration, becoming preferential areas for microcrack initiation. As the service time increases, the microcracks continue to expand and connect along the interface, forming a diffusely distributed microcrack damage network inside the panel.

[0005] Secondly, the micro-damage network accumulated during normal service can further induce the risk of combustion and structural failure of the panels under fire conditions. The thermal stress generated by the high temperature of a fire will accelerate the expansion and interconnection of existing micro-cracks inside the panels, forming interconnected crack channels extending from the interior of the panels to the surface. The epoxy resin in the debris undergoes pyrolysis upon heating, releasing combustible volatile components; some combustible gases escape along the crack channels to the surface of the panels, participating in combustion under the action of an external open flame, providing conditions for the flames to spread along the facade; another part of the volatile gases remains in the pores and cracks of the panels, forming local high pressure, further expanding the cracks, accelerating the peeling of the panel surface and the disintegration of the overall structure. It can be seen that the long-term accumulation of micro-damage caused by interface incompatibility and thermal mismatch will translate into the risk of combustion and structural failure of the panels in a fire scenario, which contradicts the fire safety requirements of integrated exterior wall insulation and decoration panels.

[0006] Therefore, how to provide a fireproof recycled composite board with waste wind turbine blade fragments as the main substrate and its preparation method, as well as how to solve the above-mentioned technical problems, is the focus of technical research in this field.

[0007] Summary of the Invention The purpose of this invention is to provide a fireproof recycled composite board with waste wind turbine blade fragments as the main substrate and its preparation method, so as to improve the problem of service-related micro-damage accumulation caused by interfacial incompatibility and thermal mismatch between blade fragments and inorganic substrates, as well as the risk of micro-crack penetration and resin pyrolysis gas generation and combustion support under fire conditions, so that the board can be used as the core layer of an integrated exterior wall insulation and decoration board, while meeting the requirements of long-term service durability and fire safety under fire conditions.

[0008] The objective of this invention is achieved through the following technical solution: A method for preparing a fire-resistant recycled composite board using waste wind turbine blade scraps as the main substrate includes the following steps: S1: Mechanically crush and screen retired wind turbine blades to obtain blade fragments; S2: Immerse the leaf fragments in a swelling solution for swelling treatment, remove them, wash them with water, drain them, and dry them at low temperature until the moisture content is less than 5%; the swelling solution includes ketone or ester solvents, water, and nonionic surfactants. S3: Immerse the scrap obtained in S2 in a silicate precursor solution and perform impregnation treatment under negative pressure or ultrasonic assistance. Remove and drain. Then immerse in a soluble chloride solution to carry out a mineralization reaction. Remove the scrap and keep it at a warm temperature for mineralization, thereby forming an inorganic mineralization layer on the surface of the blade scrap. Dry it at a low temperature of 40℃~50℃ until the moisture content is less than 5%. S4: Immerse the dried fragments obtained in S3 in a fluorosilicate solution for sealing treatment, then take them out, wash them with water, and dry them at a low temperature of 40℃~50℃ until the moisture content is less than 5%; S5: Mix the dried fragments obtained in S4 with inorganic cementitious materials, wollastonite, active magnesium oxide-microsilica composite, short-cut basalt fibers and water evenly to obtain a mixed slurry; S6: The mixed slurry is injected into a mold and cured under conditions of 20-35℃ and 50%-80% relative humidity to obtain the fireproof recycled composite board.

[0009] This invention provides a method for preparing a fire-resistant recycled composite board using waste wind turbine blade fragments as the main substrate. This method improves upon the issues mentioned in the background art, such as the accumulation of service-related micro-damage caused by interfacial incompatibility and thermal mismatch between blade fragments and inorganic substrates, as well as the problems of micro-crack penetration and resin pyrolysis-induced combustion under fire conditions. Specifically, the method is as follows: In step S1, the decommissioned wind turbine blades are mechanically crushed and screened to obtain blade fragments, providing a basic substrate with controllable morphology and particle size for subsequent surface treatment.

[0010] In step S2, a mixture of ketone or ester solvents and water, with the addition of a nonionic surfactant, is used as a swelling solution to swell the blade fragments. The ketone or ester solvents cause slight swelling of the cured epoxy resin on the surface of the fragments, increasing the surface free energy of the resin and forming micropores on the surface, facilitating subsequent adsorption and shallow penetration of silicate precursors. The addition of the nonionic surfactant reduces the interfacial tension between the swelling solution and the hydrophobic resin surface, improving the wetting and penetration uniformity of the swelling solution on the fragment surface. After the swelling treatment, the surface is rinsed with water to remove residual solvent, minimizing interference with subsequent mineralization reactions.

[0011] In step S3, the swollen fragments are first immersed in a silicate precursor solution under negative pressure or ultrasonic assistance to promote the penetration and enrichment of the precursor into the micropores of the resin surface. After draining, they are then immersed in a soluble chloride solution, where calcium or magnesium ions react with silicate ions in the pores of the resin surface to form calcium silicate or magnesium silicate in situ. This stepwise impregnation method allows the silicate precursor to be pre-enriched in the micropores of the resin surface. After draining to remove the free solution on the surface, metal cations are introduced to confine the mineralization reaction to the resin surface in situ, effectively preventing the two reactants from reacting prematurely in the solution. This results in a coating structure with an outer layer dominated by inorganic mineral phases, an inner layer dominated by organic resin phases, and a middle layer that is a transitional zone between resin and minerals. The outer inorganic mineral phase of this structure can effectively bond with subsequent inorganic cementitious materials, improving the interfacial compatibility between the blade fragments and the inorganic substrate. The transition characteristics between the outer inorganic mineral layer and the inner resin alleviate the sharp interface between fillers and the substrate in traditional composite materials, helping to mitigate stress concentration during thermal expansion and contraction, and reducing the accumulation and initiation of micro-damage. Thermal mineralization allows minerals to fully precipitate and densify on the resin surface. Simultaneously, the inorganic mineralization layer on the fragment surface can form a thermal insulation barrier at high temperatures, delaying heat transfer to the internal resin and limiting the outward diffusion of flammable volatiles generated from epoxy resin pyrolysis, reducing the risk of flame propagation.

[0012] In step S4, the mineralized fragments are immersed in a fluorosilicate solution for sealing. The fluorosilicate reacts with the soluble calcium or magnesium ions remaining in the mineralized layer to generate insoluble products such as calcium fluoride, magnesium fluoride, and silica gel. This effectively seals the residual micropores and capillary channels on the surface of the mineralized layer, reduces the capillary water absorption rate of the mineralized layer itself, and weakens the water migration at the fragment interface.

[0013] In step S5, the sealed fragments are uniformly mixed with magnesium cementitious material, wollastonite, active magnesium oxide-microsilica composite, chopped basalt fibers, and water. Wollastonite has a low coefficient of thermal expansion, which reduces the overall coefficient of thermal expansion of the inorganic substrate and minimizes thermal mismatch between the substrate and the blade fragments. Under conditions of slow moisture intrusion in the service environment of the sheet metal, the active magnesium oxide-microsilica composite reacts with the microsilica to gradually form hydrated magnesium silicate gel, which fills and repairs microcracks. Chopped basalt fibers help form random overlaps in the substrate, improving the overall flexural strength and impact resistance of the sheet metal.

[0014] In summary, through the synergistic effect of each step and component, the present invention enables the fire-resistant recycled composite board to achieve both daily service durability and fire safety under fire conditions in the application scenario of the core layer of the integrated exterior wall insulation and decoration board.

[0015] As some possible implementations of this application, in step S1, the particle size of the blade fragments is 0.5mm to 8mm.

[0016] As some possible implementations of this application, in step S2, the ketone is selected from acetone and butanone; the ester solvent is ethyl acetate; in the swelling solution, the mass ratio of ketone or ester solvent, water and nonionic surfactant is 100:40~400:0.5~5; the nonionic surfactant is selected from OP-10 (octylphenol polyoxyethylene ether) and Tween-80 (polysorbate-80); the swelling treatment temperature is 30℃~60℃, and the treatment time is 1h~4h; and the solution is dried at low temperature until the moisture content is less than 5%.

[0017] As some possible implementations of this application, in step S3, the silicate precursor is selected from sodium silicate and potassium silicate, the mass fraction of the silicate precursor in the solution is 10%~40%, and the impregnation time is 0.5h~2h; the soluble chloride salt is selected from calcium chloride and magnesium chloride, the mass fraction of the solution is 3%~10%, the mineralization reaction temperature is 10℃~25℃, and the reaction time is 0.5h~1.5h; the heat preservation mineralization temperature is 60℃~90℃, and the heat preservation time is 2h~6h.

[0018] As some possible implementations of this application, in step S3, the thickness of the inorganic mineralization layer can be controlled between 30μm and 150μm. If the thickness is less than 30μm, the mineral coating will be incomplete and the interface modification effect will be insufficient. If the thickness is greater than 150μm, the mineral layer on the surface of the crushed material will be too thick, which may lead to a decrease in the fluidity of the slurry and affect the uniformity of the plate forming. Among them, the outer inorganic mineral phase can form an effective combination with the hydration products of the cementitious material, the inner organic resin phase retains the original interface structure between the resin and glass fiber of the crushed material, and the middle layer helps to achieve a gradual transition of modulus.

[0019] As some possible implementations of this application, in step S4, the concentration of the fluorosilicate solution is 3%~10%, the sealing treatment temperature is 40℃~60℃, and the treatment time is 30min~60min. A fluorosilicate concentration in the range of 3%~10% allows it to react with residual calcium or magnesium ions in the mineralized layer. If the concentration is too low, the sealing effect will be insufficient; if it is too high, a thicker deposition layer may form on the surface of the mineralized layer, affecting the bonding between the crushed material and the cementitious material.

[0020] As some possible implementations of this application, in step S5, the inorganic cementing material is a magnesium cementing material, which is magnesium oxychloride cement, magnesium oxysulfide cement, or a mixture of the two.

[0021] As some possible implementations of this application, in step S5, the mass ratio of the dried scraps, inorganic cementitious material, wollastonite, active magnesium oxide-microsilica composite, chopped basalt fiber, and water obtained in S4 is 100:80~150:5~20:2~8:3~10:30~50. Within this mass ratio range, the inorganic cementitious material can better coat the surface of the scraps and fill the gaps between the scraps; when the amount of wollastonite is 5~20 parts, the effect of adjusting the coefficient of thermal expansion of the substrate is more obvious; when the amount of active magnesium oxide-microsilica composite is 2~8 parts, it can provide self-healing function without excessively increasing the consistency of the slurry; when the amount of chopped basalt fiber is 3~10 parts, it helps the fibers to form overlaps in the substrate; when the amount of water is 30~50 parts, the slurry has good fluidity and formability.

[0022] As some possible implementations of this application, in step S5, the mass ratio of active magnesium oxide to microsilica in the active magnesium oxide-microsilica composite is 1:1~4. A higher proportion of microsilica can provide more silicon source for the self-healing reaction, while a lower proportion of active magnesium oxide can avoid adverse effects on the substrate due to its hydration volume expansion. The active magnesium oxide-microsilica composite is prepared by physically mixing active magnesium oxide powder and microsilica powder.

[0023] In addition, the present invention provides a fireproof recycled composite board comprising a waste wind turbine blade scrap substrate and an inorganic cementitious material substrate, characterized in that the surface of the waste wind turbine blade scrap substrate has an inorganic mineralization layer formed by the swelling, stepwise mineralization and sealing treatment steps in the preparation method according to any one of claims 1 to 9.

[0024] Compared with the prior art, the beneficial effects of the present invention are: This invention uses waste wind turbine blade fragments as the main substrate. An inorganic mineralization layer is formed on the surface of the fragments through a pretreatment route of swelling-step mineralization-sealing. Wollastonite is added to adjust the thermal expansion coefficient of the substrate, an active magnesium oxide-microsilica composite provides self-healing and volume stability, and short-cut basalt fibers enhance mechanical properties. This improves the problem of incompatibility between the blade fragments and the inorganic substrate interface and the accumulation of service-related micro-damage caused by thermal mismatch. At the same time, it alleviates the risks of micro-crack penetration and resin pyrolysis-induced combustion under fire conditions.

[0025] Tests showed that the composite panels prepared in Examples 1-3 had a flexural strength of 8.5-10.5 MPa, a compressive strength of 16.8-20.3 MPa, and a microcrack count of 0-1 per 100 mm² after 50 thermal cycles. Their combustion performance reached A2 level. After 25 freeze-thaw cycles, the mass loss rate was 0.2%-0.5%, the strength loss rate was 0.9%-2.1%, the 24-hour water absorption rate was 4.1%-6.8%, and the 28-day wet curing volume expansion rate was 0.04%-0.08%. Therefore, the fire-resistant recycled composite panels prepared by this invention can balance daily service durability and fire safety under fire conditions when used as the core layer of integrated exterior wall insulation and decoration panels. Detailed Implementation

[0026] Example 1 S1: Take retired wind turbine blades (from retired glass fiber reinforced epoxy resin blades from wind farms, cut and coarsely crushed for later use) and crush them with a hammer crusher. After screening, obtain blade fragments with a particle size of 0.5mm~8mm. Take the fragments with a particle size concentrated in the range of 1mm~5mm as the base material to be processed.

[0027] S2: Mix acetone (industrial grade) and water at a mass ratio of 100:200, add 1% of a nonionic surfactant (OP-10, industrial grade) to the total mass of the mixture, and stir until homogeneous to obtain a swelling solution. Immerse the blade fragments obtained in S1 into the swelling solution, with a mass ratio of fragments to swelling solution of 1:3. Control the treatment temperature at 45℃ and the treatment time at 2.5 hours (the swelling treatment is carried out in a closed reactor equipped with a solvent condensation and recovery device to achieve organic solvent recycling, reduce volatilization loss and safety risks). After treatment, remove the fragments, wash the surface with deionized water to remove residual swelling solution, drain, and dry at a low temperature of 45℃ until the moisture content is below 5%.

[0028] S3: Prepare a 25% sodium silicate solution (diluted with water to the required concentration using industrial-grade sodium silicate solution, wherein the industrial-grade sodium silicate solution has a modulus of 3.0~3.4 and a mass fraction of 34%~38%) as the silicate precursor solution. Immerse the dried fragments obtained in S2 into the sodium silicate solution at a mass ratio of fragments to sodium silicate solution of 1:2.5, and perform impregnation treatment under ultrasonic assistance at a frequency of 40kHz for 1 hour. Remove the fragments and drain them thoroughly until no free liquid film is visible on the surface of the fragments. Then prepare a 6% calcium chloride solution (dissolved in water using industrial-grade anhydrous calcium chloride), and immerse the drained fragments into the calcium chloride solution at a mass ratio of fragments to calcium chloride solution of 1:2.5, controlling the reaction temperature at 18℃ for 1 hour. The crushed material was removed, drained, and then kept at 75℃ for 4 hours to complete the mineralization, resulting in a crushed material with an inorganic mineralization layer on the surface. This material was then dried at a low temperature of 40℃~50℃ until the moisture content was less than 5%. The thickness of the mineralization layer was approximately 80μm.

[0029] S4: Prepare a 6% (w / w) magnesium fluorosilicate solution (prepared by dissolving industrial-grade magnesium fluorosilicate in water) as the sealing treatment solution. Immerse the dried fragments obtained in S3 into the sealing treatment solution, with a mass ratio of fragments to magnesium fluorosilicate solution of 1:2.5. Control the treatment temperature at 50℃ and the treatment time at 45 min. Remove the fragments, wash them with deionized water, and dry them at a low temperature of 40℃~50℃ until the moisture content is below 5%.

[0030] S5: Preparation of magnesium cementitious material (magnesium oxychloride cement system): Mix lightly calcined magnesium oxide powder (active magnesium oxide content ≥85%, industrial grade) with magnesium chloride hexahydrate aqueous solution evenly, wherein the mass ratio of lightly calcined magnesium oxide powder to magnesium chloride hexahydrate is 2.5:1, and the concentration of magnesium chloride solution is 23% (mass fraction, prepared by dissolving industrial grade magnesium chloride hexahydrate in water).

[0031] The dried crushed material obtained in S4, the above-mentioned magnesium oxychloride cementitious material, wollastonite powder (length-to-diameter ratio 5:1~15:1, particle size 200~400 mesh, industrial grade), active magnesium oxide-microsilica composite, short-cut basalt fiber (diameter 10~15μm, length 6mm, industrial grade) and water are mixed at a mass ratio of 100:120:12:5:6:40 and stirred in a mixer at 150r / min for 10min to obtain a uniform slurry.

[0032] The preparation method of the active magnesium oxide-microsilica composite is as follows: active magnesium oxide (lightly calcined magnesium oxide powder, active magnesium oxide content ≥85%, industrial grade) and microsilica powder (SiO2 content ≥92%, specific surface area ≥15m² / g, industrial grade) are weighed at a mass ratio of 1:2 and thoroughly mixed in a powder mixer to obtain the active magnesium oxide-microsilica composite.

[0033] S6: Inject the mixed slurry into a mold made of stainless steel with an inner cavity size of 300mm × 300mm × 10mm. The inner surface of the mold is pre-coated with a water-based release agent. After injecting the slurry, vibrate it on a vibrating table for 2 minutes to remove air bubbles and smooth the surface. Cure and shape it at a temperature of 35℃ and a relative humidity of 70%. After curing at room temperature for 24 hours, demold it and continue curing it at a temperature of 25~30℃ and a relative humidity of 70% for 7 days to obtain a fireproof recycled composite board.

[0034] Example 2 This embodiment adjusts some parameters based on embodiment 1. All other parameters are the same as in embodiment 1, unless otherwise mentioned. The specific adjustments are as follows: S1: The particle size of the leaf fragments obtained by sieving is 0.5mm~3mm.

[0035] S2: The swelling solution is a mixture of methyl ethyl ketone (industrial grade) and water, with a mass ratio of methyl ethyl ketone to water of 100:400. The nonionic surfactant (OP-10, industrial grade) accounts for 0.5% of the total mass of the swelling solution. The treatment temperature is 30℃ and the treatment time is 1h.

[0036] S3: Sodium silicate solution with a mass fraction of 10% was used for ultrasonic-assisted impregnation for 2 hours (the mass ratio of the crushed material to the sodium silicate solution was 1:2.5, the same as in Example 1). Calcium chloride solution with a mass fraction of 3% was used, the reaction temperature was 10°C, and the reaction time was 0.5 hours (the mass ratio of the crushed material to the calcium chloride solution was 1:2.5, the same as in Example 1). The mineralization temperature was maintained at 90°C for 2 hours. The resulting mineralized layer was approximately 30 μm thick.

[0037] S4: Magnesium fluorosilicate solution concentration 3%, treatment temperature 40℃, treatment time 30min.

[0038] S5: The mass ratio of dried crushed materials, cementing materials, wollastonite powder, active magnesium oxide-microsilica composite, short-cut basalt fiber (3mm in length) to water is 100:80:5:2:3:30.

[0039] Preparation of activated magnesium oxide-microsilica composite: Activated magnesium oxide and microsilica were weighed at a mass ratio of 1:1 and thoroughly mixed in a powder mixer to obtain the activated magnesium oxide-microsilica composite.

[0040] Example 3 This embodiment adjusts some parameters based on embodiment 1. All other parameters are the same as in embodiment 1, unless otherwise mentioned. The specific adjustments are as follows: S1: The particle size of the leaf fragments obtained by sieving is 5mm~8mm.

[0041] S2: The swelling solution is a mixture of ethyl acetate (industrial grade) and water, with a mass ratio of ethyl acetate to water of 100:40. The nonionic surfactant (OP-10, industrial grade) accounts for 2% of the total mass of the swelling solution. The treatment temperature is 60℃ and the treatment time is 4h.

[0042] S3: A 40% potassium silicate solution (diluted with water to the required concentration using industrial-grade potassium silicate solution, with a modulus of 3.0-3.4 and a mass fraction of 28%-32%) is used for negative pressure-assisted impregnation for 0.5 hours. A 10% magnesium chloride solution (prepared by dissolving industrial-grade magnesium chloride hexahydrate in water) is used for the reaction at 25°C for 1.5 hours. The mineralization temperature is maintained at 60°C for 6 hours. The resulting mineralized layer is approximately 150 μm thick.

[0043] S4: Magnesium fluorosilicate solution concentration 10%, treatment temperature 60℃, treatment time 60 min. The mass ratio of crushed material to magnesium fluorosilicate solution is 1:2.5, the same as in Example 1.

[0044] S5: Preparation of magnesium cementitious material (magnesium sulfate-oxygen cement system): Mix lightly calcined magnesium oxide powder (active magnesium oxide content ≥85%, industrial grade) with magnesium sulfate heptahydrate aqueous solution evenly, wherein the mass ratio of lightly calcined magnesium oxide powder to magnesium sulfate heptahydrate is 2.5:1, and the magnesium sulfate solution concentration is 25% (mass fraction, prepared by dissolving industrial grade magnesium sulfate heptahydrate in water).

[0045] The mass ratio of dried crushed material, the above-mentioned magnesium oxysulfate cementitious material, wollastonite powder, active magnesium oxide-microsilica composite, short-cut basalt fiber (12 mm in length) to water is 100:150:20:8:10:50.

[0046] Preparation of activated magnesium oxide-microsilica composite: Activated magnesium oxide and microsilica were weighed at a mass ratio of 1:4 and thoroughly mixed in a powder mixer to obtain the activated magnesium oxide-microsilica composite.

[0047] Comparative Example 1: This comparative example omits the swelling treatment step S2, which is based on Example 1. That is, the blade fragments obtained in S1 are not subjected to swelling treatment and directly proceed to S3 for sodium silicate and calcium chloride impregnation. The remaining steps are the same as in Example 1.

[0048] Comparative Example 2 is based on Example 1, but omits the stepwise mineralization process S3. That is, the dried fragments obtained in S2 are not subjected to sodium silicate impregnation, calcium chloride impregnation, or heat preservation mineralization, and directly enter S4 for sealing treatment. The remaining steps are the same as in Example 1.

[0049] Comparative Example 3 is based on Example 1, but omits the heat preservation and mineralization process in S3. Specifically, after the reaction in the calcium chloride solution in S3, the crushed material is directly drained, washed, and dried without heat preservation at 60℃~90℃. The remaining steps are the same as in Example 1.

[0050] Comparative Example 4 is based on Example 1, but omits the S4 fluorosilicate sealing treatment step. That is, the dried fragments obtained in S3 directly enter S5 to mix with the cementitious material. The remaining steps are the same as in Example 1.

[0051] Comparative Example 5: Based on Example 1, the stepwise mineralization in S3 was replaced with conventional silane coupling agent treatment. Specifically, the dried fragments obtained in S2 were immersed in a 2% (w / w) ethanol solution of KH-550 silane coupling agent (commercially available industrial grade), with a mass ratio of fragments to coupling agent solution of 1:2.5, for 1 hour. After immersion, the fragments were dried at 80°C. Silicate impregnation and calcium chloride impregnation were not performed. The remaining steps were the same as in Example 1.

[0052] Comparative Example 6 is based on Example 1, except that the wollastonite powder in S5 is removed. Specifically, the mass ratio of dried crushed material, magnesium oxychloride cement, active magnesium oxide-microsilica composite, chopped basalt fiber, and water in S5 is 100:120:5:6:40. The remaining steps are the same as in Example 1.

[0053] Comparative Example 7: Based on Example 1, the active magnesium oxide-microsilica composite in S5 was replaced with an equal mass of single active magnesium oxide. Specifically, the mass ratio of dried crushed material, magnesium oxychloride cement, wollastonite powder, active magnesium oxide, chopped basalt fiber, and water in S5 was 100:120:12:5:6:40. The remaining steps were the same as in Example 1.

[0054] The fire-resistant recycled composite boards obtained in Examples 1-3 (denoted as S1-S3) and Comparative Examples 1-7 (denoted as D1-D7) were used as test samples. All samples were cut from 300mm×300mm×10mm boards prepared in the same batch. Three parallel repeated experiments were conducted simultaneously on each sample group. The average of the three parallel tests was taken as the final test result, with a relative standard deviation (RSD) ≤ 5%. The test results are shown in Table 1. The test items and methods are as follows: 1. Flexural strength test: Specimen size 250mm×50mm×10mm. Place the specimen on a universal testing machine with a span of 200mm and a loading rate of 5mm / min. Record the maximum load at which the specimen breaks and calculate the flexural strength using the three-point bending formula.

[0055] 2. Compressive strength test: Specimen size 100mm×100mm×10mm. Place the specimen on a universal testing machine and apply continuous and uniform pressure at a loading rate of 2mm / min until the specimen fails. Record the maximum failure load and calculate the compressive strength.

[0056] 3. Observation of microcracks during thermal cycling: The specimen size was 100mm × 100mm × 10mm. The specimen was placed in a 60℃ forced-air drying oven for 8 hours, and then immediately placed in a -15℃ freezer for 8 hours. This constituted one thermal cycle. After 50 thermal cycles, the specimen was removed and observed under a stereomicroscope at 20x magnification on the surface and cross-section of the plate. The number of microcracks longer than 0.5mm per unit area (10mm × 10mm field of view) was counted. Five fields of view were randomly selected from each specimen for statistical analysis, and the average value was taken.

[0057] 4. Combustion Performance Test: Combustion performance is graded according to GB 8624 "Classification of Combustion Performance of Building Materials and Products". Among them: The non-combustibility was verified by GB / T 5464 "Test Methods for Non-combustibility of Building Materials"; The total calorific value (PCS) was tested according to GB / T 14402; The combustion performance of the individual components was tested in accordance with GB / T 20284, and FIGRA, LFS, THR600s, SMOGRA, TSP600s and combustion drip / particulate phenomena were recorded simultaneously.

[0058] Test results show that the samples obtained in Examples 1-3 all meet the requirements of GB 8624 for Class A2 in terms of non-flammability, total calorific value, FIGRA index, flame lateral spread, THR600s, SMOGRA, TSP600s, and combustion drips / particulates, and their flammability performance is determined to be Class A2.

[0059] 5. Freeze-thaw cycle test: Specimen size 100mm×100mm×10mm. The freeze-thaw cycle regime is: -20℃ freezing for 4 hours, followed by water thawing at 20℃ for 4 hours, constituting one cycle. After 25 freeze-thaw cycles, the specimen is removed, and the surface is observed for frost or peeling. The mass loss rate is measured, and the flexural strength after freeze-thaw is tested. The strength loss rate is calculated.

[0060] 6. 24-hour water absorption test: Specimen size 100mm×100mm×10mm. Dry the specimen in an oven at 105℃ to constant weight, weigh the oven-dried mass, then immerse it in water at 20℃±2℃ for 24 hours. After soaking, remove the specimen, wipe off the surface water, weigh the saturated mass, and calculate the water absorption rate.

[0061] 7. Long-term wet curing volumetric stability test: Specimen dimensions 100mm×100mm×10mm. The specimens were placed in a curing room at 25±2℃ and relative humidity ≥95% for 28 consecutive days. After removal, the specimen surface was observed for micro-cracks. The changes in the length of each side of the specimen were measured using vernier calipers, and the volumetric expansion rate was calculated. Table 1: Performance test results of each sample. Note: "-" in the table indicates that the sample has experienced significant failure or performance degradation in the previous test and is not required or cannot continue to be tested.

[0062] Table 1 shows that the samples obtained in Examples 1-3 (S1-S3) improved the accumulation of service-related micro-damage caused by interfacial incompatibility and thermal mismatch between blade fragments and inorganic substrates, as mentioned in the background art, as well as the problems of micro-crack propagation and resin pyrolysis-induced combustion under fire conditions. Specifically, the flexural strength of S1-S3 was in the range of 8.5-10.5 MPa, the compressive strength was in the range of 16.8-20.3 MPa, and the number of micro-cracks after 50 thermal cycles was only 0-1 / (100 mm²), indicating that the inorganic mineralization layer alleviated the stress concentration caused by thermal mismatch between the fragments and the substrate through modulus gradual change, which helped to suppress the initiation and accumulation of micro-cracks during daily service. The combustion performance of all samples reached A2 level, indicating that the inorganic mineral skeleton formed by mineralization remained stable at high temperatures, delayed the transfer of heat to the internal resin, limited continuous pyrolysis and the large-scale escape of combustible gases, and enabled the board to still have reliable fire resistance under fire conditions. After 25 freeze-thaw cycles, no significant changes were observed on the surface, with a mass loss rate of only 0.2%–0.5% and a strength loss rate of only 0.9%–2.1%. This indicates that the fluorosilicate sealing treatment reduced the water absorption rate of the mineralized layer, thereby reducing the risk of soluble salt re-halogenation and freeze-thaw damage. The 24-hour water absorption rate was in the range of 4.1%–6.8%, and the volume expansion rate after 28 days of wet curing was only 0.04%–0.08%. This demonstrates that the active magnesium oxide-microsilica composite effectively controlled the hydration volume expansion through the dilution effect of microsilica and the replenishment of the silicon source, resulting in good long-term volume stability of the board.

[0063] In Comparative Example 1 (D1), the performance of all components deteriorated after the swelling treatment step was removed, indicating that the swelling treatment is a prerequisite for the effective penetration of the precursor. The absence of this step will lead to insufficient mineralization, and the interface improvement and resin sealing effect will be significantly reduced.

[0064] In Comparative Example 2 (D2), after the stepwise mineralization process was removed, all properties deteriorated, indicating that the absence of the inorganic mineralization layer has a serious adverse effect on mechanical properties, crack resistance and fire resistance.

[0065] Comparative Example 3 (D3) showed a significant decrease in fire resistance after the removal of the thermal insulation mineralization process, indicating that thermal insulation mineralization plays an important role in the full release of minerals on the resin surface. The absence of this step mainly affects the fire resistance under fire conditions.

[0066] Comparative Example 4 (D4) showed a significant deterioration in freeze-thaw performance after the removal of the fluorosilicate sealing process, indicating that the sealing process plays a key role in reducing the water absorption rate of the mineralized layer, reducing the return of soluble salts to brine, and reducing freeze-thaw damage.

[0067] Comparative Example 5 (D5) showed a significant decrease in mechanical and fire-retardant properties after the stepwise mineralization was replaced with a silane coupling agent. This indicates that although the coupling agent can improve interfacial bonding, it cannot form a mineral skeleton to seal and isolate the resin. Its effect in suppressing microcracks and providing fire protection is significantly inferior to the stepwise mineralization scheme of this invention.

[0068] In Comparative Example 6 (D6), the ability to resist microcracks during thermal cycling decreased after the removal of wollastonite, indicating that wollastonite makes an important contribution to adjusting the thermal expansion coefficient of the substrate and alleviating thermal mismatch.

[0069] In Comparative Example 7 (D7), after replacing the active magnesium oxide-microsilica composite with single active magnesium oxide, the volume expansion under long-term wet curing was significantly increased, and microcracks appeared on the surface of the board. This indicates that the hydration volume expansion of single active magnesium oxide had an adverse effect on the substrate, while the active magnesium oxide-microsilica composite effectively alleviated the problem through the dilution effect of microsilica and the replenishment of silicon source.

Claims

1. A method for preparing a fireproof recycled composite board using waste wind turbine blade scraps as the main substrate, characterized in that, Includes the following steps: S1: Mechanically crush and screen retired wind turbine blades to obtain blade fragments; S2: Immerse the leaf fragments in a swelling solution for swelling treatment, remove them, wash them with water, and drain them; the swelling solution includes ketone or ester solvents, water, and nonionic surfactants; S3: Immerse the fragments obtained in S2 in a silicate precursor solution and perform impregnation treatment under negative pressure or ultrasonic assistance. Remove and drain. Then immerse in a soluble chloride solution to carry out a mineralization reaction. Remove the fragments, keep them warm for mineralization to form an inorganic mineralization layer, and dry. S4: Immerse the dried fragments obtained in S3 in a fluorosilicate solution for sealing treatment, then take them out, wash them with water, and dry them at low temperature; S5: Mix the dried fragments obtained in S4 with inorganic cementitious materials, wollastonite, active magnesium oxide-microsilica composite, short-cut basalt fibers and water evenly to obtain a mixed slurry; S6: The mixed slurry is injected into a mold and cured to obtain the fireproof recycled composite board.

2. The preparation method according to claim 1, characterized in that, In step S1, the particle size of the blade fragments is 0.5mm to 8mm.

3. The preparation method according to claim 1, characterized in that, In step S2, the ketones are selected from acetone and butanone; the ester solvent is ethyl acetate; In the swelling solution, the mass ratio of ketone or ester solvent, water and nonionic surfactant is 100:40~400:0.5~5; The swelling treatment temperature is 30℃~60℃, and the treatment time is 1h~4h.

4. The preparation method according to claim 1, characterized in that, In step S3, the silicate precursor is selected from sodium silicate and potassium silicate, the mass fraction of the silicate precursor in the solution is 10%~40%, and the impregnation time is 0.5h~2h; The soluble chloride salt is selected from calcium chloride and magnesium chloride, with a solution mass fraction of 3% to 10%, a mineralization reaction temperature of 10℃ to 25℃, and a reaction time of 0.5h to 1.5h; The heat preservation and mineralization temperature is 60℃~90℃, and the heat preservation time is 2h~6h.

5. The preparation method according to claim 1, characterized in that, In step S3, the total thickness of the inorganic mineralized layer is 30μm~150μm.

6. The preparation method according to claim 1, characterized in that, In step S4, the concentration of the fluorosilicate solution is 3%~10%, the sealing temperature is 40℃~60℃, and the treatment time is 30min~60min.

7. The preparation method according to claim 1, characterized in that, In step S5, the inorganic cementing material is a magnesium cementing material, which is magnesium oxychloride cement, magnesium oxysulfide cement, or a mixture of the two.

8. The preparation method according to claim 1, characterized in that, In step S5, the mass ratio of the dried fragments, inorganic cementing material, wollastonite, active magnesium oxide-microsilica composite, short-cut basalt fiber and water obtained in S4 is 100:80~150:5~20:2~8:3~10:30~50.

9. The preparation method according to claim 1, characterized in that, In step S5, the mass ratio of active magnesium oxide to microsilica in the active magnesium oxide-microsilica composite is 1:1~4.

10. A fire-resistant recycled composite board, characterized in that, Prepared by the preparation method according to any one of claims 1 to 9.